Institutional antecedents to shareholder monitoring: The liability of localness in shareholder votes - UCHIDA, Daisuke (Institutional Knowledge at Singapore Management University, 2021)
This study explores how institutional forces shape the extent to which shareholders vigilantly monitor their invested firms. Using the context of the shareholder vote on director elections in Japan, especially focusing on a shift of institutional pressures, i.e., disclosure of voting records, we examine how its influence on the extent to which firms receive dissenting votes differs depending on their ownership structure. Drawing on institutional theory and on the concept of the liability of localness, we find that firms receive more dissenting votes after the disclosure as shareholdings by domestic investors who pay greater attention to the local constituents increase. We argue that this change derives from the liability of localness that domestic investors suffer. We further demonstrate that the relationship is pronounced under specific contingencies consistent with the agency theory principle that these constituents promote, i.e., low firm performance and the nomination of a nonindependent outside director.